ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU DENGAN MENGGUNAKAN METODE ECONOMIC ORDER QUANTITY (EOQ) DALAM MENETAPKAN PERIODIC ORDER QUANTITY (POQ) (STUDI KASUS PADA PABRIK TEMPE SOYBEAN) - Handayani, Resti; Afrianandra, Cut (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2022)
This study aims to find out how to control raw material inventory which is traditionally carried out by the Tempeh Soybean Factory by analyzing how to control raw material inventory using the Economic Order Quantity (EOQ) and Periodic Order Quantity (POQ) methods. In this study, we uses a descriptive-qualitative approach. The author uses observation, interviews, and documentation in collecting data. The resource persons in this study consisted of factory owners, assistants, and employees at the Soybean Tempeh Factory. The results of the study indicate that based on company policy using the traditional method of ordering 5.000 kg of raw materials, while using the EOQ/POQ method of 5.862 kg, there is a variant of 862 kg. The frequency of purchasing soybean raw materials was previously 12 times ordering in 3 months, while it was calculated using the EOQ/POQ method 10 times, there were 2 times variants. Safety stock in its policy is around 2.350 kg, if using the EOQ/POQ method it is 1.650 kg. The reorder point in the EOQ/POQ method is 3.600 kg, while the reorder point at the Soybean Tempeh Factory is 2.200 kg, there are variants, namely 1.400 kg. (TIC) using the traditional method of Rp. 44.335.000, while using the EOQ/POQ method the total inventory cost is Rp. 30.806,703 where there is a variant of Rp. 13.528.297.